Penyusunan Laporan Keuangan pada Yayasan Bundo Saiyo - Ferdawati; Riza Meilani Roskha; Afridian Wirahadi Ahmad; Reni Endang Sulastri (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2023)
The final report is to comprise the financial report of the Bundo Saiyo Foundation according to the general standard of financial accounting. The creation of financial statements is set by Statement of Financial Accounting no. 1 (PSAK 1) and for non-profit entities set in the Standard Interpretation of Financial Accounting no. 35 (ISAK 35). The foundation is one form of a nonprofit entity that is primarily moving toward humanity with the primary goal of not making profit. The final research object for this project is the Bundo Saiyo Foundation, which is located at the Balai Gadang, Koto Tangah district, Padang City, West Sumatra. The Bundo Saiyo Foundation has not yet compiled a financial report and has only a record of cash in and cash out, so the true value of assets, liabilities and assets is unknown. The study results in a financial report composed of comprehensive income statements, statement of changes inn equity, financial position statements and cash flow statements. With the financial report expected transparency and accountability to the Bundo Saiyo foundation.